Development of Automated Material Handling System for Small Scale Industries - Dontikurti, Raghuveer; Srihari, P; Mohana Rao, K; Siva; Balu, G; Mahesh, R (Journal of Advanced Research in Mechanical Engineering and Technology, 2022)
To study and analyze the Robots with Conveyor belt which performs the operation of picking and placing the object from one place to another place. The production is increasing day by day as the time is passing and it has become a priority of every company to speed up their production rate along with profit. When production occurs on a large scale then problem arrives in the material handling system because of so many factors like counting of products, removing the defective piece etc., Due to these reasons manufacturing units are found to be more interested towards automation via robots for their work. The main objective is to transfer materials among the automatic robots on industrial layout from machining department to storage department in an efficient manner and designed coveyor belt that was made automated and controlled with sensors to perform the task. How to cite this article: Dontikurti R, Srihari P, Rao KM, Siva, Balu G, Mahesh R. Development of Automated Material Handling System for Small Scale Industries. J Adv Res Mech Engi Tech 2022; 9(3&4): 1-5.